2012
DOI: 10.1038/ejhg.2012.41
|View full text |Cite
|
Sign up to set email alerts
|

DNA replication is altered in Immunodeficiency Centromeric instability Facial anomalies (ICF) cells carrying DNMT3B mutations

Abstract: ICF syndrome is a rare autosomal recessive disorder that is characterized by Immunodeficiency, Centromeric instability, and Facial anomalies. In all, 60% of ICF patients have mutations in the DNMT3B (DNA methyltransferase 3B) gene, encoding a de novo DNA methyltransferase. In ICF cells, constitutive heterochromatin is hypomethylated and decondensed, metaphase chromosomes undergo rearrangements (mainly involving juxtacentromeric regions), and more than 700 genes are aberrantly expressed. This work shows that DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
(51 reference statements)
1
14
0
Order By: Relevance
“…Additional molecular mechanisms acting in trans , such as perturbed nuclear organization as a result of the altered juxtacentromeric or telomeric heterochromatin organization [18-20], deregulated expression of small regulatory microRNAs (miRNA) [21] or changes in replication timing [22] may also have a deep impact on the deregulation of gene expression programs in ICF patients. However, these perturbed profiles showed great variability, probably reflecting phenotypic variability between patients and cell culture effects, and no common or distinguishing molecular signatures could be reliably established from these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Additional molecular mechanisms acting in trans , such as perturbed nuclear organization as a result of the altered juxtacentromeric or telomeric heterochromatin organization [18-20], deregulated expression of small regulatory microRNAs (miRNA) [21] or changes in replication timing [22] may also have a deep impact on the deregulation of gene expression programs in ICF patients. However, these perturbed profiles showed great variability, probably reflecting phenotypic variability between patients and cell culture effects, and no common or distinguishing molecular signatures could be reliably established from these studies.…”
Section: Introductionmentioning
confidence: 99%
“…This lets us speculate that it is adaptation to the changing environment leading to changes of epigenetic status, which in turn induce the increased nucleotide diversity. A recent study reported that replication defects, which result from chromatin changes caused by a DNMT3B mutation, can cause differences in individuals with mutations (Lana et al 2012), indicating a correlation between methylation status and mutation rates. CpG content dependent correlation between non-CpG and CpG mutations (with a threshold of ~0.53% CpG content) (Walser et al 2008; Walser and Furano 2010) also supports a role for methylation in DNA mutation.…”
Section: Resultsmentioning
confidence: 99%
“…ICF-patient fibroblasts carrying abnormally short telomeres at a low population doubling enter senescence prematurely. 47 Other observations likely related to the changes in the ICF epigenome include altered DNA replication with heterochromatic genes replicating earlier in the S-phase, 48 activation of juxtacentromeric heterochromatic genes, 49 and changes in intranuclear organization of chromosomes or chromosome domains. 50À52 DIAGNOSTICS Without cytogenetic confirmation, most patients with ICF syndrome will be classified as suffering from common variable immunodeficiency (CVID) according to the WHO classification for primary immunodeficiencies.…”
Section: Chromosomal Abnormalities Hypomethylation and Nuclear Orgamentioning
confidence: 97%